Determination of Amadori Product in Glycated Human Serum Albumin by Spectroscopy Methods. Issue 24 (27th June 2018) - Bohlooli, Mousa; Ghaffari‐Moghaddam, Mansour; Khajeh, Mostafa; Sheibani, Nader
Abstract: The Amadori product is a stable intermediate in the glycation process, and its increased formation is a marker of hyperglycemia in diabetes mellitus. Its accumulation in the body contributes to pathological complications of diabetes including diabetic nephropathy and retinopathy, and cardiovascular diseases. In this study the effect of 3‐β‐hydroxybutyrate on the production of Amadori products and structural changes of human serum albumin (HSA) after incubation with glucose was investigated using FT‐IR, circular dichroism (CD), and UV‐visible and fluorescence spectroscopy. Our results showed that the production of Amadori products in HSA incubated with glucose was decreased in the presence of 3‐β‐hydroxybutyrate. The glycation‐mediated alterations in HSA secondary and tertiary structures were also reduced in the presence of 3‐β‐hydroxybutyrate. These changes were attributed to reduced formation of glucose covalent bonds with the HSA lysine residues in the presence of 3‐β‐hydroxybutyrate. Thus, 3‐β‐hydroxybutyrate reduced the production of Amadori products by reacting with lysine residues and decreasing HSA covalent modifications by glucose. Abstract : The HSA with Glc alone, 3BHB alone and Glc+3BHB was incubated at sterile and physiological conditions for 21 days and then dialyzed. The analysis of all samples was carried out by various spectroscopic methods including FT‐IR, circular dichroism (CD), and UV‐visible and fluorescence spectroscopy. The UV‐visible results showed that the structural change of HSA and Amadori products formation decreases in the present of 3BHB.